Profile of nurses working in Family Health Units and the quality of care provided (Research, Society and Development, 2022)
The present study is of a quantitative nature, carried out with nurses who take care of Family Health Units (USF), in the city of Olinda, Pernambuco, Brazil. This work aims to verify the profile of nurses and the quality of care provided by them. Data were collected through a semi-structured questionnaire, where the analysis found that all nurses interviewed were aged between 20 and 40 years; most of these professionals were women, married, and had more than 3 years of experience in nursing care. In addition, most do not have a postgraduate degree in the Family Health Program (PSF), and say they are not confident in carrying out the procedures, and believe that the PSF strategy is well designed, but poorly implemented. The present study allowed us to better understand the profile of this type of professional and the quality of the work they provide in family health teams.